EXAMINING CORRELATES OF FIVE FACTOR MODEL PERSONALITY TRAITS OF FUTURE SPECIALISTS AND THEIR SPECIALTY PREFERENCES: A CROSS-SECTIONAL ANALYTICAL STUDY - Nouman, Fizza; Amjad, Tahira; Nasir, Malaika; Rahim, Abdur; Yousaf, Maimoona; Abid, Malaika; Gondal, Abdullah Inayat; Chaudhry, Abdullah Waheed (Journal of Ayub Medical College Abbottabad, 2025)
Background: Personality traits significantly influence medical students’ and physicians’ specialty choices. The Five Factor Model assesses extraversion, conscientiousness, openness, agreeableness, and neuroticism. Certain specialties attract individuals with specific traits, and recognizing these correlations enhances medical education and career planning. Objectives were to assess personality traits of medical students and house officers using Factor Five Model, identify their future specialty preferences and determine any correlation. Methods: This cross-sectional analytical study (n=230) was conducted among medical students from a private medical college and house officers at a tertiary care hospital in Rawalpindi, Pakistan, after ethical approval from March to August 2023. A self-administered questionnaire collected demographic data, specialty preferences, and personality traits assessed using the Big Five Inventory–2 Extra-Short Form with Cronbach’s α = 0.74. Data were analyzed on SPSS v-23 (p≤0.05). Results: Out of 230 respondents, 64.8% were females, mean age 23±1.5 years. Agreeableness had highest mean score (10.97±2.26), Neuroticism was lowest (8.70±2.49), with females scoring higher in both. Significant higher Agreeableness was linked to post-graduate study plans (p=0.028). Surgery (n=75) and Internal Medicine (n=50) were most preferred. Extraversion was significantly higher in Surgery (p=0.014) and lower in Radiology (p=0.027). Pediatrics correlated with higher neuroticism (p=0.028), family medicine with lower neuroticism (p=0.05). Emergency Medicine (p=0.018) and Ophthalmology (p=0.05) were associated with higher agreeableness. Conclusion: These findings highlight personality patterns influencing specialty choices in medical professionals. Recognizing these associations aids medical training, career counselling, and workforce planning, ensuring balanced physician distribution. Tailored guidance may enhance job satisfaction, fulfilment, and healthcare efficiency.